A Middle Age Woman with the Episodes of Excruciating Pain in the Neck and Ear - Memon, Ashfaque; Samad, Adil; Finan, Katherine (Archives of Clinical and Medical Case Reports, 2018)
A middle aged woman presented with episodes of excruciating pain in right side of neck and right ear. The pain was episodic and each episode lasting for few seconds. Multiple doses of NSAIDs, steroids and morphine had no effect over the intensity and frequency of pain. MRI brain, neck and internal auditory meatus were normal. She was reviewed by ENT and dental services and no obvious cause was detected. A clinical diagnosis of Glossopharyngeal neuralgia was made and escalating dose of carbamazepine was started which brought remarkable pain control.